Sustainable removal of arsenic from simulated wastewater using solid waste seed pods biosorbents of Cassia fistula L. - Giri D.D.; Jha J.M.; Srivastava N.; Hashem A.; Abd_Allah E.F.; Shah M.; Pal D.B. (My University, 2025)
The present investigation is focused to develop a new type of solid waste based biosorbent, derived from the Cassia fistula pod biomass. The prepared biosorbent has been characterized through different techniques including field emission scanning electron microscopy, fourier transform infrared spectroscope and X-ray diffraction to investigate the physiochemical properties which are potential for the bioadsorbent application. The experiments have been performed considering four parameters namely; pH, biosorbent dose, initial concentration of As+3 and duration in the batch reactor. The experimental results have been analyzed using the design-expert software for the optimization of different parameters. The maximum removal of arsenic could be achieved ∼91% whereas monolayer adsorption capacity is found to be 1.13 mg g−1 in 80 min at pH 6.0 and 30 °C by using 60 mg dose of bioadsorbent. The arsenic adsorption behavior of the bio-adsorbent has been well interpreted in terms of pseudo-first order and Freundlich model. © 2021 Elsevier Ltd